Hubungan Kegiatan Storytelling dengan Kemampuan Bahasa Reseptif Anak Usia Prasekolah 4-5 Tahun di Kota Surakarta - Aryani, Vidi Veranica; Perdana Putra, Sinar (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Language ability is an important thing for children, language is a tool for communicating with friends or people around them. Children's language ability, especially in the receptive category is receiving language, at the level of developmental achievement is listening to other people's words and understanding the stories that read. Objectives: This study aims to determine whether there is a correlation between storytelling activities with receptive language ability of preschool aged 4-5 years in Surakarta City. Methods: This type of research is a quantitative research. This research is an observational study with a cross sectional design. The sampling technique used was a total sampling of 37 respondents aged 4-5 years in KB/TK Aisyiyah Al Amin Bibis Luhur Surakarta. The statistical test used is Kendall Tau. Results: The results of the analysis show that the value of p = 0.006, this indicates that the value of p <0.05 means that there is a significant correlation between storytelling activities with receptive language ability of preschool aged 4-5 years. The value of the correlation coefficient (r) = 0.443 which means it has a moderate positive correlation. Conclusion: There is a correlation between storytelling activities with receptive language ability in preschool aged 4-5 years in Surakarta City. Keywords: Receptive language, storytelling, preschool aged 4-5 years.